Implikasi Sosial Pernikahan Usia Muda di Kabupaten Bone - Akhiruddin Akhiruddin (Universitas Muhammadiyah Makassar, 2017)
A young marriage is an inner bond between a man and a woman as a husband and wife for the purpose of forming a family, a happy and eternal household based on the One Supreme Godhead. This study aims to determine the impact of young marriage. This research type is qualitative decriptive, and determination of informant done with Purvosive Sampling, Technique of collecting data using observation, interview and documentation. Then analyzed by data reduction, data presentation, and verivication. The results of this study indicate that positive impacts are (1) to avoid free association, (2) lighten the life burden of one party from the family, and (3) learn to be responsible to the family and while the negative impact is (1) biologis (risk of pregnancy (2) Psychological (prolonged psychic trauma in the child's soul is difficult to cure) and (3) Sociological (immature ways of thinking that reduce harmonization in the family). (4) Population (population density) of fertile couples.Keywords: Impact, Marriage, Young Age.